Status of structural steel fabrication installation work amidst current situation of the Corona virus spread in China - Brac University (Brac University, 2023)
This record consists of general correspondence regarding status of structural steel fabrication installation work of BRAC University new campus project amidst current situation of the Corona virus spread in China.